Baseball and rhetorics of purity : the national pastime and American identity during the war on terror - Butterworth, Michael L. (Rhetoric, culture, and social critique., 2010)
Baseball has long been considered America's "national pastime," touted variously as a healthy diversion, a symbol of national unity, and a model of democratic inclusion. But, according to Michael Butterworth, such favorable rhetoric belies baseball's complicity in the rhetorical construction of a world defined by good and evil. Baseball and Rhetorics of Purity is an investigation into the culture and mythology of baseball, a study of its limits and failures, and an invitation to remake the game in a more democratic way. It pays special attention to baseball's role in the reconstruction.